Building A Consumer-Based Brand Equity Through Brand Personality In E-Commerce - Kabul Trifiyanto; Wahyuni Windasari; Tuti Zakiyah (Agregat: Jurnal Ekonomi dan Bisnis, 2021)
This study assesses the impact of the CBBE antecedent instrument of cognitive (internal consumer) and marketing (external) factors on the formation of brand equity through brand personality in e-commerce companies. The study was conducted with a quantitative approach by distributing questionnaires as many as 153 respondents who are active users and have frequently made purchases through e-commerce in Indonesia which are then processed using SPSS 25. The results of the study indicate that cognitive antecedents have a positive effect on brand personality and brand equity. Marketing antecedents in e-commerce companies in Indonesia have no effect on brand equity but have an influence on brand personality. Brand personality is proven to be able to partially mediate cognitive factors and fully mediate marketing factors on brand equity. This research provides the latest contribution to the development of a digital industry strategy to build brand equity in ecommerce companies, especially through brand personality